항공기 탑재 AESA 레이다의 공대공 모드 다표적 관리 기법 - 김용민; Yong-min Kim; 노지은; Ji-eun Roh (한국항행학회논문지, 2023)
능동위상배열레이다(AESA radar; active electronically scanned array radar)는 전자적으로 빔을 조향함으로써 빔조향 시간이 비약적으로 빨라져 기존의 기계식 빔조향 레이다에 비해 높은 추적 정확도를 갖는 다표적 처리 능력이 크게 증대되었다. 본 논문은 AESA 레이다의 다표적 상황에서 추적 표적을 효율적으로 관리하는 방안에 관한 것으로, 표적의 우선순위에 따라 표적을 전시(display)표적과 비전시 표적으로 나누고, 전시 표적은 보장하는 추적 정확도의 수준에 따라 최고우선순위, 고우선순위, 상황인식 표적으로 나눈다. 또한 표적의 우선순위를 판단할 수 있는 규칙을 제안하고, 동시운용모드를 포함한 공대공 모드 임무간 추적 표적 관리에 대해 제안하였다. 제안된 방식은 항공기 탑재 AESA 레이다에 적용하여 SIL (system integration lab) 환경에서 검증하였다. AESA radar is able to instantaneously and adaptively position and control the beam, and this enables to greatly improve multi-target tracking capability with high accuracy in comparison to traditional mechanically-scanned radar system. This paper is primarily concerned with the development of an efficient methodology for multi-target managenent with the context of multi-target environment employing AESA radar. In this paper, targets are stratified into two principal categories: currently displayed targets and non-display targets, predicated upon their relative priority. Displayed targets are subsequently stratified into TOI (target of interest), HPT (high priority target), and SAT (situational awareness target), based on the requisite levels of tracking accuracy. It also suggests rules for determining target priority management, especially in air-to-air mode including interleaved mode. This proposed approach was tested and validated in a SIL (system integration lab) environment, applying it to AESA radars mounted on aircraft.